2005
DOI: 10.1158/0008-5472.can-04-4547
|View full text |Cite
|
Sign up to set email alerts
|

ABCG2 Harboring the Gly482 Mutation Confers High-Level Resistance to Various Hydrophilic Antifolates

Abstract: ABCG2 is an ATP-binding cassette transporter that confers resistance to various chemotherapeutic agents. Recent studies have established that an Arg (wild-type) to Gly mutation at amino acid 482 in ABCG2 alters substrate specificity. Here, we explored the role of this G482 mutation in antifolate resistance using a clinically relevant 4-hour drug exposure. Stable transfectants overexpressing the mutant G482 transporter displayed 120-, 1,000-, and >6,250-fold resistance to the antifolates methotrexate, GW1843, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 25 publications
2
31
0
Order By: Relevance
“…Previous reports have established that the Arg482Gly and Arg482Thr ABCG2 mutations resulted in altered substrate specificity and augmented cellular drug resistance (Robey et al, 2003;Shafran et al, 2005;Bram et al, 2006). To determine whether these mutations alter IA substrate specificity and thereby facilitate the efflux of non-ABCG2 substrates of group B IAs, a flow cytometric IA accumulation assay was employed using HEK293 cells stably transfected with wild-type Arg482-as well as mutant Gly482-or T482-ABCG2 (Robey et al, 2003) (Fig.…”
Section: Abcg2 Confers Differential Resistance To Tas Based On the Prmentioning
confidence: 99%
“…Previous reports have established that the Arg482Gly and Arg482Thr ABCG2 mutations resulted in altered substrate specificity and augmented cellular drug resistance (Robey et al, 2003;Shafran et al, 2005;Bram et al, 2006). To determine whether these mutations alter IA substrate specificity and thereby facilitate the efflux of non-ABCG2 substrates of group B IAs, a flow cytometric IA accumulation assay was employed using HEK293 cells stably transfected with wild-type Arg482-as well as mutant Gly482-or T482-ABCG2 (Robey et al, 2003) (Fig.…”
Section: Abcg2 Confers Differential Resistance To Tas Based On the Prmentioning
confidence: 99%
“…ABCG2 confers resistance to anticancer drugs, such as mitoxantrone, doxorubicin, and daunorubicin, by decreasing their cellular accumulation, and thus, ABCG2 has been referred to as breast cancer resistant protein (BCRP) [17]. Subsequent analyses have shown that overexpression of ABCG2 results in the acquisition of resistance to anticancer drugs, such as camptothecin derivatives (topotecan [4], SN-38 [49], 9-aminocamptothecin [49]), antifolates (methotrexate and its polyglutamate form, GW1843 and tomudex) [68,79,78], flavopiridol [64], and bisantrene [46]. Attention should be paid to the acquired mutations of ABCG2 in some tumor cell lines (R482G and R482T), which have been shown to alter the spectrum of resistance to anticancer drugs.…”
Section: Abcg2 (Bcrp/abcp/mxr)mentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 4 The metabolite 7-OHMTX ( Fig. 1) results from oxidation of MTX primarily by hepatic aldehyde oxidase.…”
Section: Page 4 Of 30mentioning
confidence: 99%
“…Decreased cellular uptake via the reduced folate carrier (RFC/SLC19A1) [3] or increased active efflux mediated by ABC transporters such as the multidrug resistance-associated proteins 1-5 (MRP 1-5), the breast cancer resistance protein (BCRP/ABCG2) [4,5] and P-glycoprotein (MDR or ABCB1) [6] can lead to resistance to hydrophilic and lipophilic antifolates. The ability of cells to accumulate long chain MTX polyglutamates (MTX-PGs) is highly dependent on the activities of folylpolyglutamate synthetase (FPGS) and folylpolyglutamate hydrolase (FPGH).…”
Section: Introductionmentioning
confidence: 99%